Description of the immature stages of Glyphepomis spinosa Campos & Grazia (Hemiptera: Pentatomidae: Pentatominae: Carpocorini) - Pollo, Pietro; Greve, Caroline; Matesco, Viviana Cauduro; Grazia, Jocelia (Zootaxa, 2012)
The study of immature stages is important in phylogeny, as well to the recognition and control of pest species. Glyphe-pomis Berg is included in the tribe Carpocorini. This paper describes the morphology of eggs and nymphs of Glyphepomis spinosa Campos & Grazia. Adult specimens were collected on rice plants in Formoso do Araguaia, Tocantins, Brazil, and they were reared in the laboratory. The immatures obtained were analyzed with a light stereomicroscope and scanning electron microscope. Eggs and nymphs were measured and illustrated and/or photographed. Eggs are barrel-shaped, light green; operculum round and convex; chorion translucent, bright and granulated; aero-micropylar processes clubbed, 68 on average. All instars have oval body and obtuse tylus, surpassing jugae. In the 1st instar, head, thorax and abdominal plates are black, and abdomen is reddish brown; punctures are absent. From 2nd instar on, head and thorax are grayish with dark punctures, and the abdomen is whitish with dark-red punctures. In relation to other Carpocorini species that occur on rice, the eggs of G. spinosa resemble those of Oebalus poecilus (Dallas), a major rice pest in South America. However, nymphs of both species can be easily differentiated by their general color: in O. poecilus all instars have a dark head and thorax and red abdomen.